2020
DOI: 10.1016/j.envpol.2019.113557
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cadmium, inorganic mercury and methyl-mercury on the physiology and metabolomic profiles of shoots of the macrophyte Elodea nuttallii

Abstract: Macrophytes are known to bioaccumulate metals, but a thorough understanding of tolerance strategies and molecular impact of metals in aquatic plants is still lacking. The present study aimed to compare Hg and Cd effects in a representative macrophyte, Elodea nuttallii using physiological endpoints and metabolite profiles in shoots and cytosol. Exposure 24h to methyl-Hg (23 ng•L-1), inorganic Hg (70 ng•L-1) and Cd (281 µg•L-1) did not affect photosynthesis, or antioxidant enzymes despite the significant accumul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 55 publications
3
13
0
Order By: Relevance
“…In the present experiment, beta-tyrosine content of B. juncea roots was increased under 48 h Cd stress, in contrast, decreased under 7 d stress. Similar results were reported by Cosio and Renault [36] that tyrosine content of Elodea nuttallii was significantly increased after 24 h of Cd treatment. This suggests that tyrosine may be involved in response to 48 h Cd stress and reduce antioxidant damage in B. juncea through its accumulation.…”
Section: Amino Acidssupporting
confidence: 91%
See 1 more Smart Citation
“…In the present experiment, beta-tyrosine content of B. juncea roots was increased under 48 h Cd stress, in contrast, decreased under 7 d stress. Similar results were reported by Cosio and Renault [36] that tyrosine content of Elodea nuttallii was significantly increased after 24 h of Cd treatment. This suggests that tyrosine may be involved in response to 48 h Cd stress and reduce antioxidant damage in B. juncea through its accumulation.…”
Section: Amino Acidssupporting
confidence: 91%
“…Branched amino acids (i.e., leucine, isoleucine, and valine) are considered as precursors for some secondary metabolites, such as alkaloids and glycosides, and participate in both biotic and abiotic stress responses [36]. Previous studies reported that levels of isoleucine and valine were accumulated in Solanum nigrum roots [37] and E. nutalli shoots [36] under Cd stress. In this paper, L-isoleucine was significantly upregulated at T2/T1, but not significantly changed at T3/T1.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Similarly, the aminoacyl-tRNA biosynthesis in the aquatic plant Elodea nuttallii was affected by exposure to Cd and MeHg. 40 Aspartate, generated by transamination of oxaloacetate, a tricarboxylic acid (TCA) cycle intermediate, accumulated in cells exposed to IHg and MeHg. Aspartate serves as a precursor for the biosynthesis of other amino acids: asparagine, homoserine, threonine, lysine, and isoleucine, 39 which were also accumulated ( Figure 4).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In whole shoots, MMHg resulted in the significant regulation of 15 metabolites, while no metabolite was significantly regulated by IHg treatment. In the cytosol, IHg and MMHg exposure regulated three metabolites and four metabolites respectively [43]. Pathway analysis by the Kyoto Encyclopedia of Genes and Genomes (KEGG) of deregulated metabolites revealed that MMHg exposure resulted in biochemical changes in aminoacyl-tRNA biosynthesis, glycine, serine and threonine metabolism, nitrogen metabolism, arginine and proline metabolism, cyanoamino acid metabolism, while IHg treatment caused no significant variations at the pathway level.…”
Section: Responses At the Proteome And Metabolome Levelmentioning
confidence: 98%
“…This discrepancy might come from a lower uptake (0.19 µg•g −1 ) of MMHg in those conditions than for IHg (0.67 µg•g −1 ). Nonetheless, a few years later, the effects of the same concentrations (4•10 −10 M IHg, 1•10 −10 M MMHg 24 h resulting in 0.98 and 0.81 µg•g −1 THg respectively) were analyzed by GC-MS-and LC-MS-targeting metabolites in a way that is complementary to other molecular approaches to confirm the Hg cellular toxicity pathway in E. nuttallii (Table 1) [43]. In whole shoots, MMHg resulted in the significant regulation of 15 metabolites, while no metabolite was significantly regulated by IHg treatment.…”
Section: Responses At the Proteome And Metabolome Levelmentioning
confidence: 99%